Євген Ерліх – основоположник соціології права - Марчук, В.П. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
Статья посвящена основателю социологического направления в юриспруденции Евгению Эрлиху, кратко изложена суть и значение его социологии права, а также возникшего на рубеже ХІХ-ХХ ст. «движения за свободное право» (Freirechtsbewegung), целью которого было обоснование свободы судейского и административного усмотрения в процессе применения норм права. Более глубокий анализ, суждения и оценки даются в работах автора, указанных в списке литературы. The article is dedicated to Eugen Ehrlich, the founder of the sociological theory in jurisprudence. A brief summary of his “sociology of law” is given, along with the analysis of its importance. Also, the “free law
movement” (Freirechtsbewegung), which emerged at the end of 19th century and the beginning of the 20th
century, as the means of justifying the freedom of court and administrative discretion in their application of
legal norms is discussed. More detailed analysis, discussions and the author’s opinions on those topics are set
out in Ehrlich’s publications indicated in the list of references.